Kajian Literatur Reviu: Jaringan Sosial Masyarakat Nelayan - Achiruddin Saleh, Adnan; Hasbi; Abdullah, Suparman; Radjab, Mansyur (KOMUNIDA : Media Komunikasi dan Dakwah, 2024)
Social networks are able to open opportunities for fishing communities to expand production both internally and externally. However, various economic problems are still a challenge faced by fishing community groups. This study presents the strategy of community social networks in strengthening bonds and expanding production markets. The method used refers to Walker and Avant (2014). Social network analysis is based on research writings that have been published in the timeframe between 2010 and 2022. The data based used is Google Scholar and Doaj. The results of the analysis show that the concept of social network has nine attributes, namely interaction network, engagement networks, social capital, coastal community resilience, exposed coastal community, social network, social linking, social knowledge networks, and community cohesion. Based on these attributes, two social networks of fishing communities were created, namely ties and networks density. Ties in fishing communities are patterns of individual or community relations as group strengthening on the internal or micro scale. Network density in fishing communities is the pattern of group relations as organizational strengthening on the external scope or the meso and macro scale.